An exploratory study into student leadership and True Colors personality with learning and training. (September 2019) - Weber, Melvin R.
Abstract: This is an exploratory study examining the relationship between students' leadership profiles and personalities within their classroom performance. The participants of the study are senior level hospitality students in a human resource class. The measures are the Student Leadership Practices Inventory (SLPI) and True Colors Word Sort. Two types of data are used: 1) traditional testing results, via paper and pencil tests, and 2) performance assessments, grades on written assignments. MANOVA results suggest some significant relationships between student leadership and performance assessment. ANOVA results suggest student leadership had a significant impact on the final grade.